Gene modifiers of cystic fibrosis lung disease: A systematic review. Issue 9 (29th May 2019) - Shanthikumar, Shivanthan; Neeland, Melanie N.; Saffery, Richard; Ranganathan, Sarath
Abstract: Background: Lung disease is the major source of morbidity and mortality in cystic fibrosis (CF), with large variability in severity between patients. Although accurate prediction of lung disease severity would be extremely useful, no robust methods exist. Twin and sibling studies have highlighted the importance of non‐cystic fibrosis transmembrane conductance regulator (CFTR) genes in determining lung disease severity but how these impact on the severity in CF remains unclear. Methods: A systematic review was undertaken to answer the question "In patients with CF which non‐ CFTR genes modify the severity of lung disease?" The method for this systematic review was based upon the "Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA)" statement, with a narrative synthesis of results planned. Results: A total of 1168 articles were screened for inclusion, with 275 articles undergoing detailed assessment for inclusion. One hundred and forty articles were included. Early studies focused on candidate genes, whereas more recent studies utilized genome‐wide approaches and also examined epigenetic mechanisms, gene expression, and therapeutic response. Discussion: A large body of evidence regarding non‐CFTR gene modifiers of lung disease severity has been generated, examining a wide array of genes. Limitations to existing studies include heterogeneity in outcome measures used, limited replication, and relative lack of clinical impact. Future work examining non‐CFTR gene modifiers will have to overcome these limitations if gene modifiers are to have a meaningful role in the care of patients with CF.